Characteristics of batik patterns of Bouyei Ethnicity in Guizhou,China - Liu, Yang Yi; Shaari, Nazlina; Mohd Ali, Noor Azizi; Perumal, Velu (Badebio Biotechnololgy, 2021)
Guizhou Province is the main inhabited area of Bouyei ethnicity in China. Its distinctive wax drawing pattern reflects the temperate climate and agricultural economic and cultural characteristics and experience and technology, forming a unique national clothing culture and aesthetic consciousness. Bouyei ethnicity batik has a solid national cultural heritage and contains a wealthy original meaning and symbolic connotation. Bouyei ethnicity batik is the dynamic wisdom of the Bouyei people and the creative resources of fashion clothing design, which has a unique aesthetic value, cultural value, and development and utilization value. Firstly, by consulting relevant literature and observation, this paper understands the history and culture of the batik of Bouyei ethnicity in Guizhou. Then using the method of case study, this paper analyzes the unique theme of batik ethnic pattern and the national cultural connotation in batik pattern of Bouyei ethnicity in Guizhou. This paper expounds on the main artistic characteristics of batik patterns of Bouyei ethnicity in Guizhou from three aspects: pattern structure, pattern significance and pattern content. It provides theoretical reference and a basis for further development and design.